2015
DOI: 10.1177/0961203315598016
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile systemic lupus erythematosus: onset patterns and short-term outcome in Egyptian children, a single-center experience

Abstract: Egyptian children with SLE appear to have severe disease on presentation with high SLEDAI scores and high prevalence of lupus nephritis, but respond well to therapy with a favorable short-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
6
10
1
Order By: Relevance
“…As regard to sociodemographic data of patients, female-to-male ratio was 7:1, which refers to significance of endocrinal factors in the clinical presentation of SLE. On comparison to other Arab researches in pediatric age, it was similar to the study reported by Abdel-Hafez and Abdel-Nabi, 2015[10] (7:1), lower than the study of Bakr, 2005[11] (12:1) and higher than the study of Salah et al , 2009[12] (2.7:1) and Ali et al , 1989,[13] which was on Indian kids (4:1), Uziel et al , 2007,[14] which was on Israeli children, (5:1), and Dunget et al , 2012[15] inVietnam (4:1). Difference in gender distribution might be due to different numbers of patients, due to differences in ethnicity or due to genetic factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As regard to sociodemographic data of patients, female-to-male ratio was 7:1, which refers to significance of endocrinal factors in the clinical presentation of SLE. On comparison to other Arab researches in pediatric age, it was similar to the study reported by Abdel-Hafez and Abdel-Nabi, 2015[10] (7:1), lower than the study of Bakr, 2005[11] (12:1) and higher than the study of Salah et al , 2009[12] (2.7:1) and Ali et al , 1989,[13] which was on Indian kids (4:1), Uziel et al , 2007,[14] which was on Israeli children, (5:1), and Dunget et al , 2012[15] inVietnam (4:1). Difference in gender distribution might be due to different numbers of patients, due to differences in ethnicity or due to genetic factors.…”
Section: Discussionsupporting
confidence: 90%
“…[16] Global and rSLEDAI score have been used in our study as the predictors of disease activity. [7] The mean global SLEDAI score was 28.6 ± 21.46 and was similar to that of Abdel-Hafez and Abdel-Nabi, 2015[10] (29.95 ± 2.06), and study by Dunget et al ,[15] 2012 (23.8 ± 11.6).…”
Section: Discussionsupporting
confidence: 78%
“…It is worth noting that female predominance was less prominent in the juvenile-onset group with a male:female ratio of 7:1 as opposed to 9:1 in the adult group, and this finding is similar to several other Egyptian 3841 and international reports. 3336…”
Section: Discussionsupporting
confidence: 89%
“…57,25 Although to a lesser extent than in adult studies, the proportion of females in jSLE studies is also fairly high, ranging from 80% to 90.9%. 7,1924,2629 We have seen somewhat a lower frequency of females (77.2%) in our study compared to previous jSLE studies. Since estrogens have been shown to play a triggering role in the etiology of SLE, 30 dissimilarity of the pubertal state may be the reason for this female:male ratio discrepancy across different studies.…”
Section: Discussioncontrasting
confidence: 77%
“…The most frequently encountered manifestations in our jSLE cohort were mucocutaneous manifestations, followed by constitutional, hematological and musculoskeletal manifestations, similar to the previous studies. 1924…”
Section: Discussionmentioning
confidence: 99%